Manipulation in Philanthropic Business: When Donation Funds Are Used for Personal Gain - Yenny Febrianty; Hasmiati Hasmiati; Arief Fahmi Lubis; Viorizza Suciani Putri (Lembaga Yasin AlSys, 2025)
This study examines the vulnerabilities of philanthropy in Indonesia amid its rapid growth through digital platforms and social organizations, highlighting risks of abuse and misuse of donations. The case of Agus Salim, a victim of acid attack whose Rp1.5 billion in public donations was diverted for personal and family use, illustrates how weak regulatory oversight has triggered a trust crisis in philanthropic institutions. The research aims to analyze manipulative practices in philanthropic activities, the factors contributing to weak supervision, and the resulting legal and social implications. Using a juridical-normative method, the study draws on literature review, case analysis, and relevant regulations, including Law No. 9 of 1961, Government Regulation No. 29 of 1980, the Criminal Code, and the Electronic Transactions Law. By comparing legal norms (das sollen) with empirical practices (das sein), the findings reveal that donation funds are often transferred into personal accounts without accountability, government supervision remains inadequate, and while existing legal instruments such as Articles 372 and 378 of the Criminal Code are applicable, enforcement is slow and inconsistent. The study concludes that philanthropy should be recognized not only as a moral activity but also as a “business of philanthropy” highly vulnerable to manipulation. It underscores the urgency of regulatory harmonization, the establishment of a national philanthropic code of ethics, and the application of good governance principles. Recommendations include the adoption of open public audits and digital reporting systems to strengthen accountability and prevent future misuse.